(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article aims to present the life story of a former Brazilian guerrilla, Ana Maria Gomes, now a professor at the Federal University of Mato Grosso do Sul. In 1968 she worked in a factory, was a high school student and was a member of the student movement. That year she participated in a strike in the city of Osasco (São Paulo) and went into clandestinity, participating in the armed organization Vanguarda Popular Revolucionária (VPR). She fought against the Brazilian civil-military dictatorship that lasted from 1964 to 1984, being arrested and tortured. Her memories denounce the physical and psychological violence that the regime perpetrated in the prisons where she suffered as woman and opponent, and also reveal the gender inequality in the armed groups in which she participated.